Identifying physical and psychological risk factors for musculoskeletal pain in student musicians to tailor the curriculum: a cross-sectional study protocol - Anne-Violette Bruyneel; Clara E James; Audrey Schmid; Dung Anh Nguyen-Danse (BMJ Open)
Introduction Insufficient identification and understanding of risk factors make musicians engaging in professional practice particularly vulnerable to musculoskeletal pain. To support positive music learning and good mental, physical, and social health, student musicians need health support tailored to their needs and their instrumental practice. However, these preventive actions must be based on sound scientific approaches that reliably identify the most relevant risk factors. MuSa is a cross-sectional study examining contextual and internal risk variables associated with playing-related musculoskeletal disorders in student musicians.Method and analysis The design is a monocentric cross-sectional study involving student musicians in Bachelor’s 1, 2, 3 and Master’s 1, 2. Free-form questions will identify students’ lifestyle characteristics and work habits, and validated questionnaires will evaluate the interaction between pain due to music practice and psychological and physical risk factors. All data will first be analysed descriptively. Psychological network analysis will be used to explore the overall correlational structure of the dataset. A subgroup comparative analysis will be then applied according to the instrumental subcategories and work postures, including singers.Ethics and dissemination The full protocol was approved by the Swiss Ethics Committee ‘Commission Cantonale d’Ethique de la Recherche sur l’être humain de Genève’ (CCER, no. 2022-02206) on 13 February 2023. Outcomes will be disseminated through publication in peer-reviewed journals and presentations at conferences.